Characters of Early Childhood Manners in The Storybook Permisi - Riska Nofianti, Farhati; Wachid Bambang Suharto, Abdul; Saputra, Rizki (International Proceedings of Nusantara Raya, 2022)
This research examines the story of Excuse me book from the aspect of polite character for early childhood. Storybooks are one of the interesting media to instill in early childhood. The purpose of this study was to analyze the character of manners in early childhood in the story book entitled "Permisi". This type of research is descriptive qualitative with a textual analysis approach or library research in the form of literature review. The data source is the “Permisi” Storybook by Yoli Hemdi. Data collection using documentation. Data analysis was carried out using several methods, namely data reduction, data classification, and verification of data information. The results of the study found and identified that the character of politeness was using reading and note-taking analysis techniques